Propane-1,3-diyl bis(4-aminobenzoate) - Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
Molecules of the title compound, C(17)H(18)N(2)O(4), lie on a twofold rotation axis that passes through the central methylene C atom. The molecules adopt a `V' shape and the trimethylene unit assumes a gauche-gauche conformation. The amino N atom shows a nonplanar coordination. Adjacent molecules are connected by N-H...O hydrogen bonds into chains running along [001]. Furthermore, N-H...N hydrogen bonds connect these chains into a three-dimensional network.